Π–π Interactions Between Aromatic Groups in Amphiphilic Molecules: Directing Hierarchical Growth of Porous Zeolites. Issue 1 (31st October 2019) - Zhang, Yunjuan; Che, Shunai
Abstract: The development of hierarchical macro‐ or mesoporous zeolites is essential in zeolite synthesis because the size of the micropores limits mass transport and their use as industrial catalysts for bulky molecules. Although major breakthroughs have been achieved, fabricating crystallographically ordered mesoporous zeolites using a templating strategy is still an unsolved challenge. This minireview highlights our recent efforts on the self‐assembly of amphiphilic molecules to obtain ordered hierarchical MFI zeolites by introducing aromatic groups into the hydrophobic tail of the amphiphilic molecules. Owing to the geometric matching between the self‐assembled aromatic tails and the MFI framework, a) single‐crystalline mesostructured zeolite nanosheets (SCZNs), b) SCZNs with a 90° rotational intergrowth structure, c) a hierarchical MFI zeolite with a two‐dimensional square P 4 mm mesostructure, and d) a single‐crystalline mesoporous ZSM‐5 with three‐dimensional pores and sheetlike mesopores layered along the a ‐axis were successfully synthesized. Abstract : Growth opportunity : Aromatic segments such as biphenyl, naphthyl, azobenzene, benzene, and 1, 3, 5‐triphenylbenzene, which have strong interactions with each other in a hydrophobic chain, were introduced to the tail of an alkyl chain. The rigid segments self‐assemble to form hydrophobic centers with an ordered orientation, blocking zeolite crystal growth and geometrically matching the zeolite framework. Appended quaternary ammonium groups direct the zeolite formation.